Online broadcasting in Malaysia: an analysis of legal and regulatory framework and future reforms - Islam, Md. Zahidul; Mokhtar, Khairil Azmin; Mohd Badrol Afandi, Nor Hafizah; Islam, Md. Asraful (2020)
This paper examines the legal and regulatory framework governing online broadcasting in Malaysia. The purpose of this study is to explore and analyse the existing legal system concerning online broadcasting services in Malaysia with a view to identifying the loopholes and suggesting recommendations for possible solution. The study uses a legal and doctrinal research methodology followed by an analytical approach. In identifying and interpreting data both primary and secondary legal sources are considered. The study reveals that the current legal framework regulating online broadcasting services in Malaysia is not well structured and, in most cases, the online broadcasting contents do not comply with the existing laws and regulations of Malaysia. Hence, a comprehensive legislation is indispensable for Malaysia to regulate the online broadcasting services diligently and efficiently.